Histology‐guided protein digestion/extraction from formalin‐fixed and paraffin‐embedded pressure ulcer biopsies. Issue 2 (23rd November 2015) - Taverna, Domenico; Pollins, Alonda C.; Nanney, Lillian B.; Sindona, Giovanni; Caprioli, Richard M.
Abstract: Herein we present a simple, reproducible and versatile approach for in situ protein digestion and identification on formalin‐fixed and paraffin‐embedded (FFPE) tissues. This adaptation is based on the use of an enzyme delivery platform (hydrogel discs) that can be positioned on the surface of a tissue section. By simultaneous deposition of multiple hydrogels over select regions of interest within the same tissue section, multiple peptide extracts can be obtained from discrete histological areas. After enzymatic digestion, the hydrogel extracts are submitted for LC‐MS/MS analysis followed by database inquiry for protein identification. Further, imaging mass spectrometry (IMS) is used to reveal the spatial distribution of the identified peptides within a serial tissue section. Optimization was achieved using cutaneous tissue from surgically excised pressure ulcers that were subdivided into two prime regions of interest: the wound bed and the adjacent dermal area. The robust display of tryptic peptides within these spectral analyses of histologically defined tissue regions suggests that LC‐MS/MS in combination with IMS can serve as useful exploratory tools.